Phase transformation pathways in Ti-6Al-4V manufactured via electron beam powder bed fusion. (15th August 2021) - Davids, William J.; Chen, Hansheng; Nomoto, Keita; Wang, Hao; Babu, Sudarsanam; Primig, Sophie; Liao, Xiaozhou; Breen, Andrew; Ringer, Simon P.
Abstract: The design of additively manufactured metallic alloys with tailored mechanical properties requires a detailed understanding of the microstructural evolution throughout the printing process. In Ti-6Al-4V, this involves a complex combination of phase transformations, leading to microstructural and property variations within a single as-fabricated build. The origin of such property variations and the sequence of phase changes occurring during the cyclic heating and cooling process remain uncertain. We have studied the phase transformation pathway by following how, in particular, the β phase growth varies within the build. Samples manufactured by electron beam powder bed fusion were analysed using electron microscopy and atom probe tomography techniques. We demonstrate that a significant β phase fraction variation occurs within a given build plane. We reveal that the high-temperature β phase can be separated into two categories, depending on whether it was retained from cooling from above the β transus temperature, or nucleated below it. This is the first direct evidence of the coexistence of both types of β transformation products in Ti-6Al-4V. The abrupt cyclic nature of the additive manufacturing process is what has facilitated this unusual transformation sequence. The work provides a complete and general description of the phase transformation pathway, informed by these observations. The implication of the phase transformation pathway on hardness is discussed in relation to chemical variation and oxygen pickup. Graphical abstract: Image, graphical abstract